HEART RATE VARIABILITY ANALYSIS ON ELECTROCARDIOGRAM ( ECG SIGNALS) AND THE EFFECT OF AGE ON HEART RATE - Nahdiyya, Fina
Heart disease is one of the deadliest diseases in the world in 2019. Measuring heart rate is the simplest thing to do in diagnosing heart disease. Several things can affect heart rate, including differences in age, sex, and body mass index (BMI). This study aims to analyze the time domain heart rate variability (HRV) based on the RR interval in lead I, II, III, aVR, aVL, and aVF and to determine the effect of age, gender, and BMI on heart rate. Heart rate measurements were carried out using a portable EKG, namely the KardiaMobile 6L, which was carried out during 30 seconds of recording under resting conditions. This study's subjects were 168, with five different age groups. Group 1 (4–5 years), group 2 (6–7 years), group 3 (10- 13 years), group 4 (19-30 years) and group 5 (55-75 years). Data from KardiaMobile 6L will be stored in PDF format. Therefore, it is necessary to optimize the digitization of the ECG signal. The variations of ?t(s) used in optimizing the digitization of the ECG signal are 0.0001, 0.0005, 0.001, 0.005, 0.01, and 0.05. The results of digitizing the ECG signal stated that the minimummaximum difference decreased in the amplitude domain at ?????(s) = 0.005, 0.01, and 0.05. In the HRV time domain analysis, the variables analyzed were the average of the RR ± standard deviation intervals and the root mean square of successive differences (RMSSD) of the RR intervals. There is no difference in the RR interval values (s) for all leads, namely lead I (0.6997 ± 0.056), lead II (0.6998 ± 0.056), lead III (0.6998 ± 0.056), aVR (0.6998 ± 0.056), aVL (0.6995 ± 0.057) and aVF (0.6998 ± 0.056). In the heart rate (bpm) analysis based on age differences, the values for each group were obtained, namely group 1 (113 ± 10.9), group 2 (106 ± 10.6), group 3 (84 ± 9.2), group 4 (83 ± 9.1) and group 5 (76 ± 7.4). Thus, it can be concluded that as we get older, the heart rate will decrease. Based on gender for all age groups, it can be concluded that women's heart rates are not always higher than men’s. Based on BMI for group 4, having five categories of BMI, it can be concluded that BMI does not affect subjects' heart rate in resting conditions.